Clinical and epidemiological characteristics and outcomes of patients affected by COVID-19 in the Intensive Care Unit - Priscila da Silva Timoteo; Kleyton Santos de Medeiros; Francis Solange Vieira Tourinho (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To understand the clinical and epidemiological characteristics, outcomes, and nursing care of adult patients affected by COVID-19 in the Intensive Care Unit. Methods: This is a quantitative, retrospective, and descriptive study. The study participants were clinical and epidemiological statistical reports. Variables analyzed included age, gender, race, comorbidities, signs and symptoms, length of hospital stay, use of mechanical ventilation, medications, infections, monitoring, invasive devices, positioning, diet, comfort, and clinical outcomes. Results: The majority of individuals were men, of white race, with a mean age of 63 years, hypertensive, diabetic, and obese. The average length of hospital stay was 16 days. Most required invasive mechanical ventilation, vasopressor drugs, sedoanalgesia, and neuromuscular blockers. Conclusion: Nursing care is related to monitoring, ventilation, medication administration, installation of devices, prone positioning, diet administration, and providing comfort.